2016
DOI: 10.11604/pamj.2016.25.62.9508
|View full text |Cite
|
Sign up to set email alerts
|

Les cardiopathies de l’enfant au CHU Souro Sanou de Bobo-Dioulasso: aspects échocardiographies et thérapeutiques

Abstract: Les cardiopathies de l'enfant déterminent en Afrique un problème de santé publique difficile à prendre en charge, de part la densité de la population jeune, le faible niveau socioéconomique et l'insuffisance de plateaux techniques adaptés. Les auteurs rapportent les aspects échocardiographiques et thérapeutiques des cardiopathies de l'enfant dans le département de pédiatrie du CHUSS de Bobo-Dioulasso. Il s'agissait d'une étude transversale descriptive concernant la période de janvier 2013 à décembre 2014 (24 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…In terms of hemodynamics, type 2a and 2b CIVs were the most recovered with 64.5% as in other African studies [5] [14]. This high frequency could be explained by the noisy symptomatology of VSD at these stages motivating consultation at baseline levels.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…In terms of hemodynamics, type 2a and 2b CIVs were the most recovered with 64.5% as in other African studies [5] [14]. This high frequency could be explained by the noisy symptomatology of VSD at these stages motivating consultation at baseline levels.…”
Section: Discussionmentioning
confidence: 55%
“…This finding of powerlessness is reported by all African studies, which report a proportion of operated cases varying between 0% and 21% [5] [14] [15] [16]. This situation could be explained by the lack of a cardiac surgery center in Burkina Faso and the impossibility for the country to carry out this surgery outside the country at an excessively high cost.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…In sub-Saharan Africa, studies of paediatric heart disease seem rare and fragmentary. Tougouma et al [3] in Burkina Faso and Ngouala et al [4] in Senegal reported hospital prevalence in children of 4.3‰ and 6‰, respectively, with predominantly congenital forms. In Côte d'Ivoire, heart disease has been the subject of very few studies in children [5] [6] [7].…”
Section: Introductionmentioning
confidence: 97%
“…In children, the incidence of heart disease varies from one region to another and depends on the available diagnostic resources. In developed countries where the technical plateau is performing, the overall incidence of childhood heart disease varies between 7 and 8 per thousand with a predominance of congenital forms [2], 71% of cases [3]. In sub-Saharan Africa, studies of paediatric heart disease seem rare and fragmentary.…”
Section: Introductionmentioning
confidence: 99%